PENERAPAN KURIKULUM 2013 DI SMA DAN MA (Tinjauan Manajemen Kurikulum) - Adinata Rusmen Idris (AZKIYA, 2018)
This study aims to determine the application of the 2013 Curriculum in Senior High Schools (SMA) and Madrasah Aliyah (MA) in their curricular management review. Data regarding this study are collected through written documents in the form of printed books, journals, articles and others. The study efforts use descriptive content analysis techniques that aim to describe in detail the contents of a message or a text by describing it in full. The results of this study obtained information that efforts to implement 2013 Curriculum in High Schools and Madrasah Aliyah are part of the responsibility of education managers and stakeholders in the education sector. By adhering to the views of experts and the applicable regulations relating to Curriculum 2013 both in schools and madrasas, it is hoped that it can bridge the need for proper education governance through the application of a good curriculum. This is the portion of management as a scientific discipline that regulates the implementation of education well.